Game of the funnel: a variant of the game of the glass. - Paradisi, M.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 10-year-old boy was urgently observed due to the sudden emergence of asymptomatic red spots on his chin. The spots had appeared on the previous evening while the child watched television. The patient had been already visited in the pediatric emergency department where blood tests and coagulation tests were performed with normal results. The child, who enjoyed good health, presented on physical examination petechiae of varying size only in a rectangular area, with clear-cut borders on the chin (Fig. 1): dermoscopy (Fig. 2) showed extravasated blood in the superficial dermis. Thinking of "petechiae "ex vacuo" we immediately asked if the spots had appeared while he drew air from a glass applied on the mouth. The father intervened, saying that the problem occurred not playing with a glass but with a funnel of about 6 cm in diameter and that he applied it around the mouth plugging with a finger the outflow orifice.